Geomechanics 2005
DOI: 10.1061/40797(172)20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial and Induced Anisotropy on Initial Stiffness of Sand by Triaxial and Bender Elements Tests

Abstract: In this study, to examine the effects of the fabric anisotropy of sand specimen and the anisotropic consolidation stress on the small strain stiffness, the bender elements test and the cyclic and monotonic triaxial tests were performed on several kinds of reconstituted and undisturbed sand samples. These laboratory test results were compared to the results of in-situ seismic surveys. Test results showed that the shear wave velocity estimated from the Young's modulus on triaxial test is lower than those from be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It can be seen that G hh * is higher than G vh * with an average value of G hh */(G vh * = G hv *) = 1.9. This difference of stiffness between G hh and G vh (G hv ) is much larger than the results from sand specimens (Yamashita et al 2005). It would seem that this is because the difference of clay content and mineralogy of soil.…”
Section: Fig 4 Examples Of Input and Received Waveforms; (A) V-specmentioning
confidence: 59%
See 1 more Smart Citation
“…It can be seen that G hh * is higher than G vh * with an average value of G hh */(G vh * = G hv *) = 1.9. This difference of stiffness between G hh and G vh (G hv ) is much larger than the results from sand specimens (Yamashita et al 2005). It would seem that this is because the difference of clay content and mineralogy of soil.…”
Section: Fig 4 Examples Of Input and Received Waveforms; (A) V-specmentioning
confidence: 59%
“…The plate was glued to the internal surface of the membrane with buttonholes (rectangular-hole). The BE was glued on a metal plate through a buttonhole on the membrane using quick-drying glue, after the complete preparation of the specimen (Yamashita et al 2005). This method does not disturb the specimen, because the BE does not penetrate into the specimen.…”
Section: Bender Element Testsmentioning
confidence: 99%
“…11(a). Based on the conclusion of Yamashita et al (2005) that shear waves propagate faster in the plane parallel to the bedding plane than in the normal one, combined with equation (1), the highest stiffness anisotropy of the air pluviation sample in this study can be explained. Although the pluviation technique is carried out in the water pluviation method, it is deemed that the deposited particles are not aligned horizontally ideally compared with the grains in the air pluviation sample.…”
Section: Effect Of Spm On Stiffness Anisotropymentioning
confidence: 74%
“…Considering the double peaks of CC and the objectivity, the PP method is finally selected for the signal interpretation. For the signal excitation frequency, Yamashita et al (2005) used the averaged value from the estimated travelling times of 10, 15 and 20 kHz. In this study, it was found that the travel times decrease slightly with an increase in the frequency for the HH and VH waves.…”
Section: Triaxial and Bender Element Testsmentioning
confidence: 99%
“…On the other hand, Rampello et al [17] reported notably higher values of G max for reconstituted clayey samples compressed anisotropically compared to those compressed isotropically at the same mean effective stress (p′). Using the results of tests performed in the true triaxial apparatus equipped with bender elements, it has also been shown that the small-strain shear modulus of sands is mainly influenced by the principal stresses in the direction of wave propagation and particle motion and is nearly independent of the out of plane stress component ( [1,5,13,15,18,19,24,26,27,28]). Accordingly, the small-strain shear modulus model, Eq.…”
Section: Introductionmentioning
confidence: 98%